Live birth rate after intrauterine insemination is not different between women with lower quartile versus higher quartile normal range thyroid stimulating hormone levels - Repelaer van Driel- Delprat, C C (Hum Reprod Open, 2019)
STUDY QUESTION: Does lower quartile normal range thyroid stimulating hormone (TSH) compared to higher quartile normal range in women without thyroid hormone substitution affect live birth rate after a complete IUI treatment series? SUMMARY ANSWER: Lower quartile normal range TSH, in women without thyroid hormone substitution, does not affect live birth rate after a complete intrauterine insemination treatment series compared to higher quartile normal range TSH. WHAT IS KNOWN ALREADY: TSH is historically seen as the most sensitive test for thyroid function. Its distribution is right-skewed. Whether the preconceptional upper reference TSH values in subfertile women should be 2.5 or 4.5 mIU/L is under debate. Studies have shown that IUI patients treated with levothyroxine for TSH levels above 2.5 mIU/L show higher pregnancy rates. However, no adverse outcome is associated with untreated high normal TSH levels studied in first IUI cycles. Thyroid peroxidase antibodies have also impaired outcomes in some studies whereas others have shown an effect only in combination with high normal TSH levels. As a subgroup, patients with unexplained infertility showed increased levels of TSH. This article adds to the value of TSH evaluation and fertility outcome in four quartiles and in the context of a completed IUI treatment modus of a maximum of six inseminations. STUDY DESIGN, SIZE, DURATION: This is a retrospective cohort study in 909 women undergoing 3588 IUI cycles starting treatment between the first of January 2008 and the first of March 2012. PARTICIPANTS/MATERIALS, SETTING, METHODS: Women aged 22–45 years with TSH 0.3–4.5 mIU/L without thyroid hormone substitution were included at Amsterdam UMC, Vrije Universiteit, Amsterdam, the Netherlands, an Iodine-sufficient area. The primary endpoint was live birth. Clinical pregnancy, pregnancy loss and ongoing pregnancy were secondary endpoints. Logistic regression was used with the natural logarithm of TSH as a continuous predictor. Chi-square tests and logistic regression were used to compare groups of patients based on TSH values in four quartile TSH groups (0.3–1.21 mIU/L; 1.22–1.75 mIU/L; 1.76–2.34 mIU/L; 2.35–4.5 mIU/L) on basic characteristics and on the endpoints while adjusting for confounders. MAIN RESULTS AND THE ROLE OF CHANCE: Analysis with the natural logarithm of TSH as a continuous variable showed no association with live birth, pregnancy chance or pregnancy loss. There were no differences in any of the outcomes across the quartile TSH level ranges after regression analysis before and after adjusting for age, BMI, use of alcohol, tobacco, use or gonadotrophins, sperm count, diminished ovarian reserve, unexplained infertility and primary or secondary subfertility. The distribution of primary and secondary subfertility and smoking characteristics were remarkably different across the four groups, with proportionally the lowest prevalence of primary subfertility and the highest rate of smoking in the lowest TSH group (0.3–1.20 mIU/L). LIMITATIONS, REASONS FOR CAUTION: Unknown values of free thyroxine and thyroid peroxidase antibodies, as well as the retrospective character of the study, limit the clinical interpretability. WIDER IMPLICATIONS OF THE FINDINGS: TSH in the highest quartile range (2.35–4.5 mIU/L) in subfertile women preceding IUI is not associated with a lower live birth rate or rate of clinical and ongoing pregnancy, or with loss of pregnancies, compared to subfertile women with TSH in the lower three quartile groups after complete intrauterine insemination treatment. STUDY FUNDING/COMPETING INTEREST(S): The department of Obstetrics and Gynaecology, division of Reproductive Medicine, and of Internal Medicine, division of Endocrinology provided support. There are no competing interests. TRIAL REGISTRATION NUMBER: N/A.